2017
DOI: 10.1097/sap.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Implant Volume and Mastectomy-Specimen Volume by Measuring Breast Volume With a 3-Dimensional Scanner

Abstract: A strong correlation existed between preoperative breast volume, mastectomy-specimen volume, and implant volume. The following formulae were calculated:Mastectomy-specimen volume (mL) = 1.01 × preoperative breast volume (mL) + 9.91Implant volume (mL) = 0.90 × preoperative breast volume (mL) + 65.42Implant volume (mL) = 0.68 × mastectomy-specimen volume (mL) + 68.26This study shows that preoperative breast volume, as measured by a 3D Kinect scanner, can provide useful assistance in the preoperative choice of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Good to strong correlations were presented. 20,27,28,35 In view of this, a Pearson correlation coefficient was also performed for this study, which demonstrated a good positive correlation between measured and AVs in both positions (r = .770, P < .001 and r = .846, P < .001 for 90 and 30°, respectively). This demonstrates how a statistically significant discrepancy in the measurements of 2 methods can still report a good correlation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Good to strong correlations were presented. 20,27,28,35 In view of this, a Pearson correlation coefficient was also performed for this study, which demonstrated a good positive correlation between measured and AVs in both positions (r = .770, P < .001 and r = .846, P < .001 for 90 and 30°, respectively). This demonstrates how a statistically significant discrepancy in the measurements of 2 methods can still report a good correlation.…”
Section: Discussionmentioning
confidence: 88%
“…The majority of volumetric studies of the breast in the literature have measured absolute breast volume using a single-captured surface, which can be used in clinical applications such as preoperative measurements to guide implant sizing or to assess asymmetry. 8 Validation studies have compared measured volumes to the weight or volume of breast tissue removed at mastectomy (mastectomy specimen volume) as their gold standard, 9,20,[26][27][28] and this study design has been seldom disputed. However, as Losken et al 9 pointed out, the different methods of volume assessment measure different areas of the breast, with MRI volumetry corresponding most closely with mastectomy specimen volume by using anatomical breast boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Publications in scientific literature describe different methods to achieve direct assessment of the breast volume and many studies tried to provide a more evidence-based approach in order to help selecting the prosthetic implant and to use this information to better plan the preoperative phase of the reconstruction [7][8][9][10][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…in 2017 was performed in a Japanese population undergoing two-stage breast reconstruction. 10 Breast volumes were measured using the Microsoft Kinect 3D scanning technology and found that pre-operative breast volumes were very similar to mastectomy and implant volumes. Clinically, this finding diverges from our daily observations, whereby mastectomy weights (and thus, implant sizes) are larger than pre-operative breast size assessments.…”
Section: Introductionmentioning
confidence: 99%